The analysis of wood harvesting restrictions in conservation areas and intact forest landscapes of the Arkhangelsk oblast - Gerasimov, Yuri; Markovsky, Alexander; Il ina, Olga; Dobrynin, Denis (Finnish Forest Research Institute, 2008)
An earlier analysis published in 2007 as Working Papers of the Finnish Forest Research Institute 56 Analysis of the current state and wood harvesting restrictions in officially existing and planned conservation areas as well as unofficial intact forest landscapes of the Arkhangelsk oblast is provided in this report. Intact forest landscapes are suggested by NGOs and these forests do not have wood harvesting restrictions according to the Russian legislation. However, environmentally responsible forest industry companies have voluntarily agreed not to procure wood from these forests.In the beginning April 2008, Arkhangelsk oblast has 106 official conservation areas with a total area of 6.5 million ha. However, several reserves, such as the large reserve Frants-Iosif Land located in Baretsevo sea islands, are out of forest fund of Arkhangelsk oblast. The total area of the forest-related conservation areas is 2.2 million ha (7.6% of the total forest fund of Arkhangelsk oblast). All types of fellings are prohibited in 11 official conservation areas (0.6 million ha or 2.1% of the forest fund of Arkhangelsk oblast). Final fellings (or clearcut) are prohibited in 51 official conservation areas (1.6 million ha or 5.4% of the forest fund of Arkhangelsk oblast). The rest of the conservation areas (28600 ha or 0.1% of the forest fund of Arkhangelsk oblast) have no restrictions for wood harvesting, but clearcut is forbidden according to current Forest Code. Two officially planned conservation areas (5.3 million ha) have been clearly recognized; however only the Onezhskoye Pomorye national park (180400 ha or 0.6% of the forest fund of Arkhangelsk oblast) is located within forest fund of the region and has restrictions for wood harvesting. NGOs have suggested 11 separate areas of intact forest landscapes (approximately 9.5 million ha or 32.4% of the forest fund of Arkhangelsk oblast). The major areas of intact forest landscapes are located in Leshukonsky, Mezensky, Severodvinsky, Onezhsky, Karpogorsky, Krasnoborsky, ...